Statistical Optimization of Controlled Porosity Osmotic Tablet of Milnacipran HCl - Ratnakar, Nayankumar C. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The objective of this study was to identify critical formulation parameters affecting the drug release from controlled porosity osmotic tablet of milnacipran hydrochloride employing the concept of design of experiments. Materials and Methods: The optimized amount of ethocel (X1) and mannitol (X2) in core and percentage of sorbitol (X3) in coat were determined employing a three-factor, three-level Box-Behnken design. A direct compression technique was employed for preparing the core tablets. The tablets were coated with cellulose acetate. The in vitro drug release study was carried out in an acidic medium (pH 1.2) for 2 h and thereafter the dissolution study was conducted in phosphate buffer (pH 6.8). Results and Discussion: The selected dependent variables were the cumulative percentage of milnacipran hydrochloride dissolved after 1 (Y1), 8 (Y2), 16 (Y3), and 24 h (Y4). Correlating the independent variables with dependent variables were evolved. Optimization was performed for the three independent variables using the decided target ranges; Y1≤20%; Y2=45 ± 5%; Y3=72 ± 5%; Y4=100%. The optimized amounts of ethocel (X1), mannitol (X2), and percentage of sorbitol (X3) were 30, 100, and 30, respectively. Conclusion: The optimized formulation showed a release profile that was close to the predicted values. The drug was released by anomalous diffusion from the optimized formulation.